2013
DOI: 10.1097/aci.0b013e328364ddfd
|View full text |Cite
|
Sign up to set email alerts
|

Expression of antimicrobial peptides in atopic dermatitis and possible immunoregulatory functions

Abstract: From the recent literature, there is considerable evidence that AMPs are induced in the skin in atopic dermatitis. However, some studies suggest that the induction, release or mobilization of some AMPs in atopic dermatitis may not reach sufficient levels to provide adequate control of cutaneous microbial colonization. Th2 cytokines appear to negatively influence the expression and induction of some AMPs. A number of immunoregulatory functions have been described for several AMPs. Most of them point to a proinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 42 publications
3
38
0
2
Order By: Relevance
“…The down-regulation of inducible AMPs/HDPs in AD has been attributed to the inhibitory effects of overexpressed Th2 cytokines on these peptides 101) . This finding is also supported by the observation that neutralization of Th2 cytokines resulted into elevated expression of hBD-2, hBD-3 and LL-37 in AD skin 103) . In contrast, Kisich et al reported that the mobilization of hBD-3 on S. aureus is impaired in AD patients compared with healthy subjects because of excess amounts of Th2 cytokines that interfere with antimicrobial activity 104) .…”
Section: Amps/hdps In Adsupporting
confidence: 76%
“…The down-regulation of inducible AMPs/HDPs in AD has been attributed to the inhibitory effects of overexpressed Th2 cytokines on these peptides 101) . This finding is also supported by the observation that neutralization of Th2 cytokines resulted into elevated expression of hBD-2, hBD-3 and LL-37 in AD skin 103) . In contrast, Kisich et al reported that the mobilization of hBD-3 on S. aureus is impaired in AD patients compared with healthy subjects because of excess amounts of Th2 cytokines that interfere with antimicrobial activity 104) .…”
Section: Amps/hdps In Adsupporting
confidence: 76%
“…It is still controversial whether AMPs are increased or decreased in atopic dermatitis lesional skin (16)(17)(18)(19). Although there have been considerable numbers of articles showing increased AMP expression in atopic dermatitis lesional skin, recent reports indicate that induction, release, and mobilization of AMPs in atopic dermatitis skin do not reach sufficient levels to provide adequate control of cutaneous microbial colonization (20). T H 2 cytokines appear to negatively influence the expression and induction of some AMPs (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Jest ona uwalniana przez eozynofile, których napływ do ognisk zapalnych w skórze stymulują cytokiny uwalniane przez limfocyty Th2 [7], a także przez zapalne komórki dendrytyczne naskórka (IDECs) napływa-jące do naskórka w trakcie zapalenia [8]. Wykazano także w krwi obwodowej chorych na AD podwyż-szone stężenie Th17, natomiast w wycinkach skór-Dermatology Review/Przegląd Dermatologiczny 2017/2 thesized by these lymphocytes activate the expression of antimicrobial peptides (AMP), TNF-α and IL-8 in the epidermis, which escalates the inflammatory state [10]. The Th17 response is especially prominent in iAD [11].…”
Section: Wprowadzenieunclassified
“…Syntetyzowane przez te limfocyty IL-17 i IL-22 aktywują ekspresję białek przeciwbakteryjnych (AMP), TNF-α i IL-8 w naskórku, przez co nasila się stan zapalny [10]. Odpowiedź typu Th17 jest szczególnie wyraźna w iAD [11].…”
Section: Wprowadzenieunclassified